Sex difference, growth pattern, and cephalic index of Turi ducks at different ages based on head morphometry - Bangun Nur Wijaya; Yeni Dhamayanti; Sri Mulyati; Soeharsono Soeharsono; Sunaryo Hadi Warsito; Sri Hidanah (Universitas Airlangga, 2024)
This study aims to determine the morphometric differences in the head of male and female Turi ducks. Ten male and ten female day-old ducks (DOD) were randomly selected by a lottery system from the population, raised, and had their head morphology measured using a digital caliper with an accuracy of 0.01 mm on the first day, and at the age of 2, 4, 6, and 8weeks. The result showed that male Turi duck had wider (p <0.05) head at the ages of 1 day, 2 and 6 weeks, head length and head height at the ages of 1 day, 2, 4, 6, and 8 weeks, rostrum width at the ages of 1 day, 4, 6, and 8 weeks, and rostrum length at the age of 2, 4, 6 and 8 weeks. There were no significant differences (p >0.05) in the head width at the ages of 4 and 8 weeks, rostrum width at 2 weeks, and rostrum length at 1day old male and female Turi ducks. Morphometric growth pattern showed that older Turi ducks (at a range of 1 day to 8 weeks) had larger (p <0.05) head morphometry. However, the cephalic index in male and female Turi ducks was not significantly different (p > 0.05) at all ages. It could be concluded that in general head morphometry was useful for determining male and female Turi ducks at the ages of 1 day, 2, 4, 6, and 8 weeks